548. Antiretroviral Therapy Regimen Characteristics Within an Urban, Safety-Net Clinic in the United States. (26th November 2018) - Hawkins, Kellie; Mclees, Margaret; Rowan, Sarah; Beum, Robert; Burman, William J; Gardner, Edward
Abstract: Background: Contemporary antiretroviral-therapy (ART) regimens have simple dosing, low toxicity, minimal side-effects, and few drug interactions. We evaluated ART regimens in an urban, safety-net, adult HIV clinic in the United States to determine proportions of patients on contemporary ART and identify opportunities to optimize ART for patients on older regimens. Methods: Data including current ART regimen, HIV-1 RNA level, and age were extracted from the electronic medical record (EMR) for all patients seen in the prior 13 months. Viral suppression was defined as HIV-1 RNA < 200 copies/mL. A patient was "off-ART" if there were no fills within 270 days or ART had a stop date >90 days prior to end of the study. Unclear regimens from the EMR ( n = 179) were chart reviewed. ART regimens were assigned the following designations: contemporary first-line, contemporary non-first-line, older three-drug, two-drug, salvage, or off-ART. ART was also categorized as boosted (containing cobicistat/ritonavir) vs. unboosted, by single-tablet regimen (STR) vs. multi-tablet regimen (MTR), and frequency of dosing. Correlations between ART regimen, viral suppression, and age were analyzed. Results: The ART review included 1, 215 individuals. Most patients (64%) were on contemporary first-line regimens; 20% were on contemporary non-first-line regimens (figure). Patients on salvage regimens had lower rates of viral suppression than those in other ART categories (80% vs. 90%, P < 0.05). Most patients (90%) were prescribed once daily regimens, and of those, 39% were prescribed STRs. There were no significant associations between viral suppression and regimen complexity ( P = 0.8). There were 447 (37%) patients on boosting agents with no difference in viral suppression rate (88% suppressed on boosted regimens vs. 90% on unboosted, P = 0.3). Patients on older regimens and greater than equal to twice daily MTRs were older than those on contemporary regimens and STRs. Individuals off ART were younger than those on ART (average age 41 vs. 46 years). Conclusion: In a US urban, safety-net clinic, most patients were on contemporary ART regimens and 90% were on once-daily therapy. Despite these encouraging findings, systematic review identified many patients that could be considered for modernization and simplification with intent to minimize toxicity, side-effects, drug interactions, and cost. Disclosures: All authors: No reported disclosures.